2009
DOI: 10.1016/j.bbmt.2009.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Conditioning Regimen in Allogeneic Hematopoetic Stem Cell Transplantation for Children with Acute Myelogenous Leukemia beyond First Complete Remission: A Pediatric Blood and Marrow Transplant Consortium (PBMTC) Study

Abstract: Total body irradiation (TBI)-based conditioning regimens for pediatric patients with acute myelogenous leukemia (AML) beyond first complete remission (CR1) are controversial. Because the long-term morbidity of busulfan (Bu)-based regimens appears to be lower, determining efficacy is critical. We retrospectively evaluated 151 pediatric patients with AML beyond CR1, comparing outcomes in 90 patients who received a TBI-based conditioning regimen and 61 patients who received a Bu-based conditioning regimen. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
3
24
1
Order By: Relevance
“…25 After stratification by acute leukemia type, they concluded in favor of TBI-based one with lower rate of relapse and best TRM. But, as with Sisler et al, 22 they have some concern regarding TBI in children and the same interrogations regarding the possible benefit of IV-BU. In another slightly older metaanalysis comparing the use of Bu-Cy vs TBI-Cy regimen in patients with either acute or chronic leukemia, TBI regimen seemed to be superior to Bu-Cy regimen with significant results for OS, TRM and relapse.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…25 After stratification by acute leukemia type, they concluded in favor of TBI-based one with lower rate of relapse and best TRM. But, as with Sisler et al, 22 they have some concern regarding TBI in children and the same interrogations regarding the possible benefit of IV-BU. In another slightly older metaanalysis comparing the use of Bu-Cy vs TBI-Cy regimen in patients with either acute or chronic leukemia, TBI regimen seemed to be superior to Bu-Cy regimen with significant results for OS, TRM and relapse.…”
Section: Discussionmentioning
confidence: 97%
“…In the Sisler et al retrospective international multi-center study published in 2009 that analyzed 241 pediatric patients transplanted for AML in CR2 or more, the authors reported no differences for both OS and of relapseincidence between Bu-based and TBI-based conditioning regimen in pediatric patients transplanted for AML beyond CR1. 22 In multivariate analysis, conditioning regimen did not independently influence rates of OS, EFS, relapse or TRM. Nevertheless, the authors claimed their preference for Bu-Cy-based conditioning regimen because of possible expected lower rate of severe and late complications after BU than after TBI as described in different papers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown no advantage of using a TBI-based preparative regimen on the outcome of children with AML in second CR [12]. These results should be interpreted with caution because the use of TBI was based on local institutional protocols in each center.…”
Section: Discussionmentioning
confidence: 67%
“…Based on these findings, children with FLT3/ITD are generally referred for allogeneic HSCT in CR1 with the best available donor. Published reports on the outcome of children with high-risk AML after allogeneic HSCT do not address the impact of FLT3/ITD on the posttransplantation outcome [1,11,12]. We sought to examine the outcome for all children with FLT3/ITDepositive AML who underwent allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%